Glucocorticoids Promote the Onset of Acute Experimental Colitis and Cancer by Upregulating mTOR Signaling in Intestinal Epithelial Cells - Zhang, Zhengguo (Cancers (Basel), 2020)
The therapeutic effects of glucocorticoids on colitis and colitis-associated cancer are unclear. In this study, we investigated the therapeutic roles of glucocorticoids in acute experimental ulcerative colitis and colitis-associated cancer in mice and their immunoregulatory mechanisms. Murine acute ulcerative colitis was induced by dextran sulfate sodium (DSS) and treated with dexamethasone (Dex) at different doses. Dex significantly exacerbated the onset and severity of DSS-induced colitis and potentiated mucosal inflammatory macrophage and neutrophil infiltration, as well as cytokine production. Furthermore, under inflammatory conditions, the expression of the glucocorticoid receptor (GR) did not change significantly, while mammalian target of rapamycin (mTOR) signaling was higher in colonic epithelial cells than in colonic immune cells. The deletion of mTOR in intestinal epithelial cells, but not that in myeloid immune cells, in mice significantly ameliorated the severe course of colitis caused by Dex, including weight loss, clinical score, colon length, pathological damage, inflammatory cell infiltration and pro-inflammatory cytokine production. These data suggest that mTOR signaling in intestinal epithelial cells, mainly mTORC1, plays a critical role in the Dex-induced exacerbation of acute colitis and colitis-associated cancer. Thus, these pieces of evidence indicate that glucocorticoid-induced mTOR signaling in epithelial cells is required in the early stages of acute ulcerative colitis by modulating the dynamics of innate immune cell recruitment and activation.